(untitled) (Third Sector Social Economic Review, 2024)
The meaning of work has a significant place in literature due to its effects on business or working life. However, the study is considered important because the number of studies examining psychological counseling skills and the meaning of working together is quite limited. The primary goal of this study is to investigate the relationship between school counselors’ counseling skills and work meanings in terms of various variances, as well as to demonstrate the power of counseling skills to explain the meaning of their work. The study was designed using a correlational study.The participants consisted of 201 counselors selected by the convenience sampling method, working at various school levels and cities in Turkey in the 2021–22 academic year. As a data collection tool ""The Counselling Self Estimate Inventory (COSEI),"", ""The Work and Meaning Inventory (WAMI),"" and the ""Personal Information Form,"" which were developed by the researchers. According to the findings obtained as a result of the analysis, there is a positive statistical relationship between counseling skills and meaning of work.Once the counselors’ counseling competence scores improve, their meaningful work scores improve as well. Counseling skills and meaningful work differ according to professional seniority, clients and supervisory support (or satisfaction). The number of clients provided at the undergraduate level affects psychological counseling skills at a high level. The findings of the study were examined in the context of previousstudies.